SUPPORTIVE CARE IN ONCOLOGY. - MERCADANTE, SEBASTIANO (CAMBRIDGE SCHOLARS PUBLIS, 2020)
This text considers the concepts of cancer pain, palliative care and supportive care, leading the reader on an evolutionary journey parallel to changes in these disciplines. It highlights new research in these fields, reflecting the link between clinical activity, primordial intuitions, and scientific data.